2016
DOI: 10.12659/msm.902179
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Analysis on Influencing Factors of Adjacent Segment Degeneration After Cervical Fusion

Abstract: BackgroundTo explore the related influencing factors of adjacent segment degeneration (ASD) after cervical discectomy and fusion (ACDF).Material/MethodsA retrospective analysis of 263 patients who underwent ACDF was carried out. Cervical x-ray and magnetic resonance imaging (MRI) were required before operation, after operation, and at the last follow-up. General information and some radiographic parameters of all patients were measured and recorded. According to the imaging data, patients were put into one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Nunley et al [29] reported that osteopenia (OD = 9.35) and documented lumbar degenerative disc disorder (OD = 5.13) were two independent risk factors for ASD in patients undergoing total disc replacement. Yu et al [30] found that older age, poor restoration of postoperative cervical lordosis, and a plate to disc distance less than 5 mm may result in ASD after cervical fusion. Lee et al [31] revealed that patients with one- or two- level anterior arthrodesis and those who smoked were more likely to receive an adjacent segment surgery within 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nunley et al [29] reported that osteopenia (OD = 9.35) and documented lumbar degenerative disc disorder (OD = 5.13) were two independent risk factors for ASD in patients undergoing total disc replacement. Yu et al [30] found that older age, poor restoration of postoperative cervical lordosis, and a plate to disc distance less than 5 mm may result in ASD after cervical fusion. Lee et al [31] revealed that patients with one- or two- level anterior arthrodesis and those who smoked were more likely to receive an adjacent segment surgery within 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [19] considered that non-operated segments increased ROM in order to maintain physiological activities after ACDF, where ROM gradually decreased cranially and caudally with a center of the operated segments. In this condition, ASD was incidental with adjacent segments overloaded.…”
Section: Discussionmentioning
confidence: 99%
“…So they considered that to prevent adjacent segment degeneration, the PDD should be 5 mm or more if possible. In addition, Yu et al 25 agreed that PDD < 5 mm is a risk factor for ASD by the logistic regression analysis based on 138 patients. However, Yang et al 26 retrospectively reviewed 218 patients who underwent anterior cervical arthrodesis with plating and considered that there is no correlation between PDD and the incidence of ASD, but PDD > 5 mm could avoid the development of adjacent segment ossi cation.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been reported that the use of short PDD plate will accelerate the degeneration of adjacent segments, eventually result in symptomatic ASD 25 .…”
Section: Discussionmentioning
confidence: 99%